Characterization and source identification of PM2.5-bound polycyclic aromatic hydrocarbons (PAHs) in different seasons from Shanghai, China - Liu, Yankun; Yu, Yingpeng; Liu, Min; Lu, Min; Ge, Rongrong; Li, Shuwen; Liu, Xinran; Dong, Wenbo; Qadeer, Abdul (The Science of the total environment, 2018)
PM2.5 samples in four representative periods were collected from a highly industrialized district in Shanghai, China. The concentrations of PM2.5 and PM2.5-bound PAHs were analyzed. Positive matrix factorization (PMF) model was used to identify the potential sources. Relationship between PAHs distribution and meteorological parameters was assessed meanwhile. The incremental lifetime cancer risks (ILCRs) model was applied to quantitatively evaluate the exposure risk of PAHs. Hybrid Single Particle Lagrangian Integrated Trajectory (HYSPLT) model was used to track the potential pollution area of PM2.5 along with a Potential Source Contribution Function (PSCF) and Concentration Weighted Trajectory (CWT) methods. The results showed concentrations of PM2.5 and PAHs ranged from 14.83 to 185.58 μg/m3, 2.58 to 123.62 ng/m3, respectively. The source apportionment model indicated that traffic emissions were the most important sources in each sampling season, which accounted for 38.44%, 34.48%, 39.04% and 45.03%, respectively. Spearman correlation coefficient showed that PAHs had negative correlation with ambient temperature and relative humidity in some periods, while had no significant correlation with atmospheric pressure and visibility. The average estimated lifetime cancer risk for total PAHs reached 4.7 × 10−5, 4.5 × 10−5 and 4.1 × 10−5, 4.0 × 10−5 to exposed children and adults in winter and autumn, respectively, meaning that PM2.5-bound PAHs had high potential risk. HYSPLIT model suggested that monsoon greatly influenced the air quality in both winter and autumn. [Display omitted] •PM2.5 concentrations were obviously higher than US air quality standards.•PMF identified traffic emissions as the major source of PM2.5-bound PAHs.•The relationship between PM2.5 and PAHs was positive.•ILCRs indicated high cancer risks in autumn and winter.•HYSPLIT showed monsoon greatly influenced the PM2.5 concentrations.